Phylogenetic position and relationships of mountain loaches (Teleostei: Balitoridae) of the Western Ghats as revealed by CO1 sequences - Sidharthan, Arya; Raghavan, Rajeev; Anoop, V. K.; Keskar, Ashwini; Dahanukar, Neelesh (Zootaxa, 2021)
The teleostean family Balitoridae comprises small-sized freshwater fishes adapted to swift-flowing torrential mountain streams in South and South-East Asia. Little is known about their molecular phylogenetics and evolutionary biogeography, and much of the scientific literature that references them is focused on morphological taxonomy. In this paper, we generate CO1 sequences for the endemic balitorid lineages of the Western Ghats (WG) Hotspot in India, particularly for the endemic genera, Bhavania, Ghatsa and Travancoria. Integration of these data into a phylogeny revealed that the endemic WG genera together form a well-supported monophyletic clade that shows, subject to our limited taxon sampling, a sister-group relationship to the Southeast Asian genus Pseudohomaloptera. Three WG endemic species of the genus Balitora, namely B. chipkali, B. jalpalli and B. laticauda, though morphologically distinct, have low genetic divergence and barcode gap, suggestive of recent speciation. Interestingly, a fourth WG endemic, B. mysorensis, formed a clade with two species of Balitora from Eastern-Himalaya and Indo-Burma. We also show that all available CO1 sequences assigned to WG endemic balitorid genera in GenBank are misidentifications, and provide diagnostic characters for the accurate identification of these taxa in the future.